Forms of Legal Protection Against Commercial Violation of Tiktok Video Copyright - Amy Firsta Dewi; Dipo Wahyoeono Hariyono (Activa Yuris: Jurnal Hukum, 2023)
This research has the aim of explaining the form of legal protection for TikTok video content which is republished without the consent of the creator or TikTok creator for commercial personal gain, one example of which is being used for advertising. This is because there is still a lack of understanding on how to take action against or report individuals who violate Intellectual Property Rights on Copyrights that have harmed creators/authors/copyright holders. Information technology has an important influence on Intellectual Property Rights, information technology updates that are increasingly developing have a positive impact on Intellectual Property Rights as well. Creators can utilize and use information technology to create works, one example is creating video content on the TikTok application. Human intellectual skills can create a work in the fields of technology, science, art and literature referred to as intellectual property to obtain legal protection in accordance with statutory regulations in the field of Intellectual Property Rights (IPR) which can be owned by individuals, groups and companies. Works in the form of moving images or short videos published in the TikTok application are one of the cinematographic works that receive legal protection under the Copyright Law. But now there is one negative impact that is increasingly prevalent, namely the misuse of the download feature provided by the TikTok application to take video content works and take advantage of personal interests in the form of advertisements without the consent of anyone. The actions of the responsible party can harm the creator/creator/copyright holder who does not get the slightest royalty and doesn't even receive an apology